Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1039/b822962g
|View full text |Cite
|
Sign up to set email alerts
|

A microfluidic chip for electrochemical conversions in drug metabolism studies

Abstract: We have designed a microfluidic microreactor chip for electrochemical conversion of analytes, containing a palladium reference electrode and platinum working and counter electrodes. The counter electrode is placed in a separate side-channel on chip to prevent unwanted side-products appearing in the measured spectrograms. Using this chip, cyclic voltammograms are measured in volumes of 9.6 nL. Furthermore the conversion efficiency of ferricyanide is characterized using UV/vis-spectroscopy. We have obtained an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(43 citation statements)
references
References 26 publications
2
40
0
Order By: Relevance
“…We have already shown that a microfluidic electrochemical cell can be used successfully (Odijk et al, 2009) to study, e.g., the metabolic pathway of amodiaquine, a known antimalarial agent. The major benefits of using a microscale electrochemical cell is that diffusion lengths are greatly reduced.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have already shown that a microfluidic electrochemical cell can be used successfully (Odijk et al, 2009) to study, e.g., the metabolic pathway of amodiaquine, a known antimalarial agent. The major benefits of using a microscale electrochemical cell is that diffusion lengths are greatly reduced.…”
Section: Introductionmentioning
confidence: 99%
“…The previous chip (Odijk et al, 2009) contained a palladium pseudo-reference electrode. Using this metal, the fabrication process is limited to temperatures up to 500 • C. At temperatures above 500 • C the palladium thin-film starts to agglomerate.…”
Section: Introductionmentioning
confidence: 99%
“…We obtained a sensitivity of 0.42 nA/µM cm −2 and a detection limit of 216 µM for glutamate, a sensitivity of 0.46 nA/µM cm −2 and a detection limit of 115 µM for glucose, a sensitivity of 1.09 nA/µM cm −2 and a detection limit of 115 µM for lactate. Few works [15], [16] deal with multiple detection of metabolites in cell cultures and none of them has shown the integration of multiple and nanostructured WEs sharing common counter and reference electrode. Instead, the results presented in this work represent a novelty with respect to the state-of-the-art in cell culture monitoring and pave the way to new integrated systems for cell analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, minimizing interferences with cells is much more desirable. Few works [17], [18] deal with multiple detection of metabolites in cell cultures and none of them has shown the integration of multiple and nanostructured working electrodes sharing common counter and reference electrodes. CITSens Bio sensors (C-CIT, Switzerland) are the only device in the market able to perform real-time cell monitoring, even if they do not allow multiple detection on the same platform.…”
Section: Metabolite Detection In Cell Culture Mediummentioning
confidence: 99%